2019
DOI: 10.1063/1.5098595
|View full text |Cite
|
Sign up to set email alerts
|

A study of surface defects in Tb doped ZnO nanoparticles for gas sensing applications

Abstract: New goals for providing better solutions with the help of nanotechnology have emerged from the electronics industry. Nano-electronics has focused on the structural, optical, magnetic, and photoluminescence properties of nanomaterials for developing optoelectronic devices. These properties play a vital role at the nanoscale level in comparison to that of bulk compounds. The use of semiconductor materials has always been in demand. Here, we are focusing on the unique and distinct structural and optical propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Concerning the expressed broadened O 1s XPS peaks (Figure S5), the peak split procedure revealed the presence of two components, and it is confirmed that the one with the higher energy corresponds to the oxygen vacancies . According to our research, ,, the peak area, corresponding to oxygen vacancies, can be taken into account as one of the structural parameters of the samples.…”
Section: Resultssupporting
confidence: 67%
“…Concerning the expressed broadened O 1s XPS peaks (Figure S5), the peak split procedure revealed the presence of two components, and it is confirmed that the one with the higher energy corresponds to the oxygen vacancies . According to our research, ,, the peak area, corresponding to oxygen vacancies, can be taken into account as one of the structural parameters of the samples.…”
Section: Resultssupporting
confidence: 67%
“…The XRD pattern shows the presence of peaks related to ZnO without any secondary impurities, denoting the phase purity of the ZnO structure. The absence of the Tb dopant peaks denotes that the thin films are highly crystalline and the added Tb dopants are interstitially incorporated into the ZnO lattice [28]. It is also observed that the intensity of the predominant plane (002) increases when the Tb dopant concentration is increased to 1%, indicating the increased crystallinity.…”
Section: Xrd Analysismentioning
confidence: 98%
“…In the previous works of our group, an n -propanol gas sensor based on the LaFeO 3 /La 2 O 3 heterostructure exhibited a high response value of 4.3 toward 1 ppm n -propanol gas . From the aspect of element doping, the enhancement of gas-sensing performances, including response value and stability, , through the doping of rare earth elements in metal oxides has been widely reported. Meanwhile, ZnO, as an n-type semiconductor, finds diverse applications in catalysts, , nanogenerators, , electroluminescence, , and gas sensors. , Inspired by these advantages, a 5% La-ZnO film was prepared that demonstrated a higher response value (400%) to 500 ppm H 2 gas compared to pure ZnO (80%) . Zhao et al prepared Ce-doped ZnO nanowires, which were exposed to 100 ppm ethanol, and exhibited a higher response (25.3) than pure ZnO (7.4) .…”
Section: Introductionmentioning
confidence: 97%